Tingkat Pendidikan, Pendapatan, Dan Pola Asuh Orang Tua Terhadap Kejadian Stunting Pada Balita - Solihin, Yasmin Salsabila; Sari, Citra Windani Mambang; Shalahuddin, Iwan; Rahayuwati, Laili; Eriyani, Theresia (Journal of Telenursing (JOTING), 2024)
This research aims to identify the relationship between education, income, and parenting patterns with the incidence of stunting among toddlers in Sukamulya Village. The research method used is quantitative correlational and uses secondary data. The research results showed that the Chi-square test obtained a p-value (α = 0.05) on the stunting variable with the father's education of 0.831, the mother's education of 0.209, the parents' income of 0.011, and the parents' parenting style of 0.614. The conclusion is that there is a significant relationship between parental income and the incidence of stunting among toddlers in Sukamulya Village. At the same time, the level of the father's education, the mother's education, and parenting patterns do not have a significant relationship with the incidence of stunting. Keywords: Toddlers, Income, Education, Parenting Patterns, Stunting